2012
DOI: 10.2460/javma.241.8.1059
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen toxicosis in dogs and cats: 145 cases (2004–2010)

Abstract: Clinical signs of baclofen toxicosis occurred in most patients, with the CNS being the system most commonly affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…Lethal doses for dogs have not been established, but the ASPCA APCC database has reported mortality in dogs at estimated doses of 8-16 mg/kg (Wismer, 2004), while Bates et al (2013) reported a case of poisoning in a dog that ingested a dose of 25 mg/kg. Death was also reported in an 8 week old dog that ingested a dose of 2.3 mg/kg (Table 5), indicating that the amount of baclofen ingested should not be used solely as a predictor of outcome (Khorzad et al, 2012).…”
Section: Muscle Relaxantsmentioning
confidence: 89%
See 1 more Smart Citation
“…Lethal doses for dogs have not been established, but the ASPCA APCC database has reported mortality in dogs at estimated doses of 8-16 mg/kg (Wismer, 2004), while Bates et al (2013) reported a case of poisoning in a dog that ingested a dose of 25 mg/kg. Death was also reported in an 8 week old dog that ingested a dose of 2.3 mg/kg (Table 5), indicating that the amount of baclofen ingested should not be used solely as a predictor of outcome (Khorzad et al, 2012).…”
Section: Muscle Relaxantsmentioning
confidence: 89%
“…hypothermia, dyspnoea and respiratory arrest may occur (Campbell and Chapman, 2000;Wismer, 2004). Several cases of intoxication of dogs by baclofen following accidental ingestion of owner's tablets have been reported (Campbell and Chapman, 2000;Wismer, 2004;Scott et al, 2007;Torre et al, 2008;Khorzad et al, 2012;Bates et al, 2013;Caloni et al, 2014). In most cases, dogs develop severe clinical signs, often despite low dosage;~15% died (Campbell and Chapman, 2000).…”
Section: Muscle Relaxantsmentioning
confidence: 94%
“…Additionally, the patient exhibited signs consistent with benzodiazepine withdrawal after abrupt discontinuation of a midazolam CRI. Based on the past literature, response to treatment has been noted shortly after institution of therapy [4][5][6][7][8] This case suggests that in patients with high dose ingestions and minimal initial response to therapies, further treatment should not be considered fruitless. When provided with ongoing intensive treatment and care, the long-term prognosis can still be excellent.…”
Section: Resultsmentioning
confidence: 99%
“…The cat that received the higher dose failed to survive, and the survival status of the cat receiving the lower dose was not known. Clinical signs of baclofen toxicosis occur in 92 per cent of cats and dogs following ingestion, and include CNS depression, vomiting, ataxia, vocalisation, coma, lethargy and hypersalivation (Wismer 2004, Scott and others 2007, Torre and others 2008, Khorzad and others 2012). A definitive diagnosis of baclofen toxicosis was not possible in the present case due to the unavailability of toxicological testing for this drug in veterinary patients; however, the history and rapid response to appropriate treatment were very suggestive of this.…”
Section: Discussionmentioning
confidence: 99%